Samples search and study of ceramics in jewelries, gemstones and in history, arts and modern society - Boo, Ting Fong. (2012)
The age of earth is around 4.5 billion years, and it is evidenced by the oldest rock of ~ 4.3 billion years. The earth crust consists of > 80% ceramics majorly in the forms of rocks, sands and soils. Ceramics have played crucial roles in human-being history, social evolvement, and culture and arts developments. Diamond, emerald, ruby and jade are only a few samples of ceramic gems and jewels. Electronic ceramics have conduction behaviours from insulators, to semiconductors, to metallic conductors, to superconductors, and ionic conductors; and have many other very attractive properties such as opto-electrical property, thermoelectricity, ferroelectricity, piezoelectricity, magnetic property, electrochemistry, etc. They have been widely used as sensors, actuators, transducers, and many electronics devices.